Aspect Oriented Requirement Engineering: A Theme Based Vector Orientation Model - Majumdar, Dipankar; Bhattacharya, Swapan (INFOCOMP Journal of Computer Science, 2010)
Separation of Concerns, in the field of Software Engineering has been an important issue for quite some time. And this issue is very much related to Aspect Oriented Software Development. This is so because Aspects happen to be certain concerns that get interleaved with the Core-Functionalities in such a way that they become nearly inseparable. As a result of which both the designer as well as the programmer, who are supposed to be concerned only with the Core-Functionalities, is bound to take extra burden or botheration regarding the proper and accurate handling of Aspects. The Theme approach is an already established approach for Aspect identification in the requirements-engineering phase. Our approach is a diversification of the Theme approach where we look for Aspectual Requirements instead of Aspectual Themes. This paper proposes a purely mathematical model for Requirements-Engineering for Aspect Identification. The concept is based on N-Dimensional-Vector-Orientation Model, which is used to serve the purpose.